Síndrome nefrótico en un recién nacido - Ccorahua-Rios, Maycol Suker; Atamari-Anahu, Noé; Lezama-Ferro, Berioska; Quispe-Curo, Rodrigo; Béjar-Yabar, Valeria; Yabar-Galdos, Gloria Janeth (Revista Médica Herediana, 2019)
.